Pengujian Fama & French Three Factor terhadap Return Saham Perusahaan Jasa yang Terdaftar di Indeks IDX80 Saat Pandemi Covid-19 - Agustin, Sheilla Putri; Nidar, Sulaeman Rahman; Kurniawan, Meinanda (Jurnal Manajemen, 2022)
This study shows the Fama & French Three Factors of weekly stock returns during the pandemic. Of the three variables, only the market variable has a significant effect on returns and has the strongest influence. Meanwhile, the variable size, book to market and the number of Covid-19 cases are not significant to the return. Simultaneously, market variables, size, book to market and the number of Covid-19 cases together or simultaneously have an influence on returns. The magnitude of the simultaneous influence of these variables is 31.02%.